EFEKTIVITAS TRAINING CAMP INTERNASIONAL TERHADAP PENINGKATAN KONDISI FISIK ATLET KURASH - Suwarli; Candra Kurniawan; Jaya Sumantri, Riyan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of international training camp programs on improving the physical condition of Kurash athletes of Lampung Provincial Government. The program was carried out for 14 days at the Thailand National Sport University with a complex training approach and high-intensity interval training (HIIT) specific to combat sports. The study used a quasi-experimental design with a pre-test and post-test approach without a control group. The subjects of the study were 10 elite athletes (age 20.5 ± 2.3 years). Variables measured included strength, power, speed, agility, cardiorespiratory endurance (VO₂max), and flexibility. Data analysis was conducted using a paired sample t-test and effect size calculation (Cohen's d). The results showed a significant increase in all physical components (p < 0.001) with a very large effect size category (d > 1.7). Average improvements include strength (23.7–31.2%), power (12.1%), speed (6.7%), agility (7.6%), endurance (7.6%), and flexibility (23.4%). These findings show that international training camps with a structured training system and sports science-based load monitoring are effective in optimizing the physiological adaptation of Kurash athletes in a relatively short time